Genome‐wide transcriptomic changes reveal the genetic pathways involved in insect migration - Toby Doyle; Eva Jimenez‐Guri; Will L. S. Hawkes; Richard Massy; Federica Mantica; Jon Permanyer; Luca Cozzuto; Toni Hermoso Pulido; Tobias Baril; Alex Hayward; Manuel Irimia; Jason W. Chapman; et al. (Molecular Ecology, 2022)
Insects are capable of extraordinary feats of long‐distance movement that have profound impacts on the function of terrestrial ecosystems. The ability to undertake these movements arose multiple times through the evolution of a suite of traits that make up the migratory syndrome, however the underlying genetic pathways involved remain poorly understood. Migratory hoverflies (Diptera: Syrphidae) are an emerging model group for studies of migration. They undertake seasonal movements in huge numbers across large parts of the globe and are important pollinators, biological control agents and decomposers. Here, we assembled a high‐quality draft genome of the marmalade hoverfly ( Episyrphus balteatus ). We leveraged this genomic resource to undertake a genome‐wide transcriptomic comparison of actively migrating Episyrphus , captured from a high mountain pass as they flew south to overwinter, with the transcriptomes of summer forms which were non‐migratory. We identified 1543 genes with very strong evidence for differential expression. Interrogation of this gene set reveals a remarkable range of roles in metabolism, muscle structure and function, hormonal regulation, immunity, stress resistance, flight and feeding behaviour, longevity, reproductive diapause and sensory perception. These features of the migrant phenotype have arisen by the integration and modification of pathways such as insulin signalling for diapause and longevity, JAK/SAT for immunity, and those leading to octopamine production and fuelling to boost flight capabilities. Our results provide a powerful genomic resource for future research, and paint a comprehensive picture of global expression changes in an actively migrating insect, identifying key genomic components involved in this important life‐history strategy.

Making the invisible visible: tracing the origins of plants in West African cuisine through archaeobotanical and organic residue analysis - Julie Dunne; Alexa Höhn; Katharina Neumann; Gabriele Franke; Peter Breunig; Louis Champion; Toby Gillard; Caitlin Walton-Doyle; Richard P. Evershed (Archaeological and Anthropological Sciences, 2022)

Resource quality determines the evolution of resistance and its genetic basis - Katherine E. Roberts; Sean Meaden; Stephen Sharpe; Suzanne Kay; Toby Doyle; Drew Wilson; Lewis J. Bartlett; Steve Paterson; Mike Boots (Molecular Ecology, 2020)
Parasites impose strong selection on their hosts, but the level of any evolved resistance may be constrained by the availability of resources. However, studies identifying the genomic basis of such resource‐mediated selection are rare, particularly in nonmodel organisms. Here, we investigated the role of nutrition in the evolution of resistance to a DNA virus (PiGV), and any associated trade‐offs in a lepidopteran pest species ( Plodia interpunctella ). Through selection experiments and whole‐genome resequencing, we identify genetic markers of resistance that vary between the nutritional environments during selection. We do not find consistent evolution of resistance in the presence of virus but rather see substantial variation among replicate populations. Resistance in a low‐nutrition environment is negatively correlated with growth rate, consistent with an established trade‐off between immunity and development, but this relationship is highly context dependent. Whole‐genome resequencing of the host shows that resistance mechanisms are likely to be highly polygenic and although the underlying genetic architecture may differ between high and low‐nutrition environments, similar mechanisms are commonly used. As a whole, our results emphasize the importance of the resource environment on influencing the evolution of resistance.

Knock‐on community impacts of a novel vector: spillover of emerging DWV‐B from Varroa ‐infested honeybees to wild bumblebees - Robyn Manley; Ben Temperton; Toby Doyle; Daisy Gates; Sophie Hedges; Michael Boots; Lena Wilfert (Ecology Letters, 2019)
Novel transmission routes can directly impact the evolutionary ecology of infectious diseases, with potentially dramatic effect on host populations and knock‐on effects on the wider host community. The invasion of Varroa destructor, an ectoparasitic viral vector in Western honeybees, provides a unique opportunity to examine how a novel vector affects disease epidemiology in a host community. This specialist honeybee mite vectors deformed wing virus (DWV), an important re‐emerging honeybee pathogen that also infects wild bumblebees. Comparing island honeybee and wild bumblebee populations with and without V. destructor , we show that V. destructor drives DWV prevalence and titre in honeybees and sympatric bumblebees. Viral genotypes are shared across hosts, with the potentially more virulent DWV‐B overtaking DWV‐A in prevalence in a current epidemic. This demonstrates disease emergence across a host community driven by the acquisition of a specialist novel transmission route in one host, with dramatic community level knock‐on effects.

Origins and genetic conservation of tropical trees in agroforestry systems: a case study from the Peruvian Amazon - Ian K. Dawson; Peter M. Hollingsworth; Jeff J. Doyle; Steve Kresovich; John C. Weber; Carmen Sotelo Montes; Terrence D. Pennington; R. Toby Pennington (Conservation Genetics, 2008)